ANALISIS KETERBACAAN WACANA PADA BUKU TEKS BAHASA INDONESIA SEKOLAH MENENGAH PERTAMA MENGGUNAKAN GRAFIK FRY - Yulia Adiningsih; Hetty Patmawati; Nina Nina (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Textbook research is an important so that the quality of text books is always maintained. The purpose of this study is to describe and report the results of an analysis of the readability or feasibility of Indonesian textbooks that are widely used in schools in Indonesia. This study uses a qualitative descriptive method with observation techniques. The collected data were analyzed according to the symptoms assessed in the study and then described. The results of the study concluded that 44.4% were in the appropriate category, 33.3% were in the inappropriate category, and 22.2% were in the invalid category.